3D optical profilometry with a double beam - splitter setup - Çetin, İsra Merve. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
In this thesis, it is demonstrated that a double beam splitter arrangement is very convenient and more practical to generate square shaped fringe patterns, and fringe distribution can be easily controlled in two dimensions. This enables to extract 3D height distribution of test objects without using any additional component as a projection unit. To approve the validity of the proposed technique, various frequencies of the fringe pattern are obtained by rotating a cubic beam splitter, and images that include deformed fringe patterns due to the height distribution of test objects are captured by a CCD camera. The resultant square fringe pattern is analyzed with two-dimensional continuous wavelet transform method and is separated into two fringe patterns in horizontal and vertical axes with a certain algorithm. The height-related phase map is acquired after analysis process.
Keywords: Optics.; Nonlinear optics.